Effectiveness of DBC Active Spine® and Hydrotherapy Interventions on Pain and Disability Due to Non-Specific Low Back Pain - Muhamad Ali Jafar (The Avicenna Medical Journal, 2023)
Background: Low Back Pain (LBP) is one of the most common painful condition that leading to disability and become a major public health problem. Non-specific low back pain   accounts for almost 90% of all cases. This study aims to determine the effects of land-based exercise using Documentation Based Care (DBC) Active Spine® and Hydrotherapy interventions on pain and disability due to Non-specific Low Back Pain (NLBP).Methods: A Quasi-experimental study on 24 samples obtained using a purposive sampling technique by considering the inclusion and exclusion criteria. The first and second groups consisted of 12 samples each receiving the hydrotherapy and DBC Active Spine® intervention. Measurement of pain and disability using the VAS and MODI instruments was carried out in the first intervention and the sixth intervention. The paired sample t-test was used to see the effect of each DBC Active Spine® and Hydrotherapy intervention on pain and disability. Independent sample t-test was used to see if there was a significant difference between the two interventions in reducing pain and disability. Results: The normality and homogeneity tests showed that the data obtained were normally distributed and had a homogeneous variance. DBC Active Spine® showed significant results on VAS and MODI which p-value=0.001 (the mean changes in VAS and MODI were 2.58 ± 0.90 and 13.33 ± 11.82, respectively). Hydrotherapy intervention showed statistically significant in VAS and MODI with p-values of 0.002 and 0.001 respectively (the mean changes in VAS and MODI were 2.33 ± 0.98 and 27.83 ± 9.00). Independent Sample T-Test showed insignificant results. The mean difference in VAS was 0.25 ± 0.38 (p-value 0.752), while the mean difference in MODI was 14.5 ± 4.3 ( p-value 0.277). Conclusion: DBC Active Spine® and Hydrotherapy interventions have a significant effect on reducing pain and disability in NLBP patients. There was no statistically significant difference between the two interventions.